2020
DOI: 10.5006/3523
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Zinc Covered with Native Oxides Under Thin Solution Films

Abstract: This study clarified the influence of native oxides on the atmospheric corrosion of Zn. The electrochemical impedance spectroscopy (EIS) values of native-oxide-covered Zn were measured under thin solution films of 10 μm to 500 μm in thickness. The native oxides were formed by exposing pure Zn plates to humidified air at two different temperatures, 25°C and 60°C, for the duration of one week. EIS was applied to the native-oxide-covered Zn for measurement under thin solution films; the results were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…P Spathis and I Poulios (1995) [19] investigated the corrosion and photo-corrosion of zinc anodic films prepared on zinc surface in borate electrolyte and reported that the film thickness is the key to protection of substrate zinc under illumination, however it has no effect in the dark. The report by C Somphotch et al (2020) [20] pointed out the importance of the thickness of electrolyte film on the surface of native ZnO film on its corrosivity, in which situation the amorphous ZnO films are more protective than crystalline ZnO films. Nevertheless, it is recognized from the above studies that galvanized steel has not yet been tested to distinguish the effects of anodizing parameters for their effects on anti-corrosion performance, and its relation to film thickness, morphological structures, and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…P Spathis and I Poulios (1995) [19] investigated the corrosion and photo-corrosion of zinc anodic films prepared on zinc surface in borate electrolyte and reported that the film thickness is the key to protection of substrate zinc under illumination, however it has no effect in the dark. The report by C Somphotch et al (2020) [20] pointed out the importance of the thickness of electrolyte film on the surface of native ZnO film on its corrosivity, in which situation the amorphous ZnO films are more protective than crystalline ZnO films. Nevertheless, it is recognized from the above studies that galvanized steel has not yet been tested to distinguish the effects of anodizing parameters for their effects on anti-corrosion performance, and its relation to film thickness, morphological structures, and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%